Repetição e correção no Facebook: uma análise - Spósito, Elias da Silva (2014)
This job has the purpose of investigate cases of repetition and amendment in texts from the social network Facebook, using as theoretical base studies of these texts with an outlook in socio cognition and interaction. For the purpose sought, it was selected a corpus of messages from Facebook, written by Digital Natives users and not Digital Natives users. The results show that in both groups the users resort to the repetition and to the amendment, in many forms and functions, to externalize their everyday life to their friends in the social network. Moreover, the use of repetitions and amendments is highlighted as a strategy to contribute to the interaction between Facebook users